Cover Image, Volume 11, Issue 7. (July 2017) - Mattioli‐Belmonte, M.; De Maria, C.; Vitale‐Brovarone, C.; Baino, F.; Dicarlo, M.; Vozzi, G.
Abstract : The cover image, by M. Mattioli‐Belmonte et al., is based on the Research Article Pressure ‐ activated microsyringe (PAM) fabrication of bioactive glass – poly(lactic ‐ co ‐ glycolic acid) composite scaffolds for bone tissue regeneration, DOI:10.1002/term.2095 . Supported by the ERC ‐ BOOST project " Biomimetic trick to re ‐ balance osteoblast ‐ osteoclast loop in osteoporosis treatment: a topological and materials driven approach ", GA 681798 ‐ PI Prof. Chiara Vitale‐Brovarone.